The role of academy fiqh in reviving the islamic law - أمیر حسین بن محمد نور; عبد الودود مصطفى مرسي السعودي (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2010)
Many Muslim scholars have realized-in the modern era- the conspiracy to exclude Islamic law from being a law of the country to Muslim countries. They also realized that the number of important issues and cases in human life which no opinion and ijtihad were made to resolved the issues. The complexity and cross disciplined of these issues made it difficult to find an answers in the fiqh’s books of heritage. Therefore, they saw the need to revive the collective ijtihad and regard it as the best way of ijtihad; because of its comprehensiveness, depth in knowledge and methodology. It is the best way to organize the Muslim scholar’s group and continue theirijtihad’s activity and it is called fiqh academy. We have seen many call by the Muslim scholars in our time to establish fiqh academy in the same way as other scientific academies – such as Arabic Language Academy – in order to achieve the objective of Muslims who feel the need to renew the Islamic jurisprudence and it development. Hopefully, this academy will become a mechanism to promote a collective ijtihad which at the same time does not remove the individual ijtihad. Thus, it is essential to carried a fundamental research on the role of academy of fiqh in renewing Islamic fiqh. The discussion will be carried out from various angles such as the definition of academy of fiqh, it objectives, its establishment and independence, its activities, and the discussion on the existing academy such as the Islamic Research Academy in Cairo, The Council of Islamic Fiqh in Mecca and the Academy of Islamic Fiqh in Jeddah. There are several findings of this research which are; firstly, the best means to implement a collective ijtihad is through academy of fiqh which comprises the mujtahidin from the entire Muslim countries as well as scholars from various human sciences and specialization. Secondly, the academy of fiqh should strive to achieve several objectives which are paying a great attention to the problems of the ummah and providing appropriate solutions, striving to unify the legislation of all Muslim countries in order to be a means unifying the ummah and enriching the Islamic jurisprudence. Thirdly, The Academy of fiqh should adhere to the set of general principles which make it a beacon of knowledge and the basis of the Islamic renaissance as well as the academy should distance itself from whims and denomination of any governmental authority. It should also has an independence opinion and freedom of expression. It also must be inclined towards the ummah rather than government. Finally, it must also free itself from any political, economical and sociological pressures